The Dialect of Varzuga and Its Neighbours - Post, Margje (University of Helsinki, 2006)
Comparisons between dialects tell us how a dialect relates to other dialects: how isolated it is, and which dialects it is most closely related to. Areal-linguistic studies also give information about the historical ties of the dialect and its speakers to other regions and about their cultural background. The present article discusses the relation of the Russian dialect of Varzuga, an old Pomor settlement on the coast of Kola Peninsula, to its Russian and Finno-Ugric neighbours.